When Social Pressure Challenges Football Athletes’ Mental Health: Lombok Collectivistic Culture as a Moderating Variable - Ari, M.Azy’; Badu, Khumaira Marsyahidah; Abdullah, Catur Prima Eka Putra; Azhari, Haeruddin (STKIP PGRI Trenggalek, 2026)
Social pressure in competitive sport is generally positioned as a psychological risk factor contributing to athletes’ mental distress. However, within collectivistic cultural contexts, social pressure may be interpreted as a form of social responsibility and group loyalty that strengthens athletes’ adaptive capacity. This study aimed to examine the effect of social pressure on the mental health of local football athletes in West Nusa Tenggara and to investigate the moderating role of collectivistic culture in this relationship. The study employed a quantitative approach with an explanatory causal design involving 83 active football athletes participating in local competitions in 2026. The research instruments were adapted from previous studies and analysed using PLS-SEM. The findings revealed that social pressure had a positive and significant effect on athletes’ mental health (β = 0.488; p < 0.001). Collectivistic culture also demonstrated a positive effect on mental health (β = 0.294; p = 0.009) and significantly strengthened the relationship between social pressure and mental health (β = 0.139; p = 0.035). These findings indicate that social pressure is not always destructive, but may function as an adaptive stressor within cohesive and collectivistic social environments. This study contributes to the cross-cultural sport psychology literature by emphasising the importance of local socio-cultural contexts in the development of athletes’ mental health and psychological well-being programmes